Formation of organizational management culture - Liu Haiwei (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the processes of forming and optimizing organizational management culture in banks. The subject of research includes the processes of organizational culture development in a modern bank during wartime and their impact on enhancing its financial stability. The purpose of the master's thesis is to identify the main factors influencing a bank's organizational culture and assess its effectiveness in ensuring financial stability under martial law conditions. Based on the results of the research, theoretical and practical provisions have been formulated regarding the optimization of organizational culture management systems for bank personnel. Practical significance of the research results: The findings offer actionable insights and tools for improving organizational culture management systems, particularly under challenging conditions such as martial law. By implementing these recommendations, banks can enhance their internal cohesion, operational resilience, and financial stability.
Scientific advisor: Cherniavska I., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; organizational culture; strategic management; management culture; management efficiency